Challenges and opportunities for plastic versus mixed waste enterprises in Greater Accra and Kisumu: A qualitative study - Ruby Hornuvo; Eunice Emefa Boafor; Lorna-Grace Okotto; Joseph Okotto-Okotto; Mawuli Dzodzomenyo; Moses Asamoah; Jim Wright (PLoS ONE, 2026)
Consumption of products packaged in plastics is growing in Sub-Saharan African cities, whose populations often lack solid waste management (SWM) services. The informal sector often fills gaps in plastic waste collection and recovery that are not met by formal SWM. To reduce plastic waste mismanagement and its associated health risks, SWM systems are needed that separate plastic waste for reuse or recycling. However, little is known about the contributions and challenges facing the mixed formal-informal enterprises in such cities’ SWM chains. This multi-country qualitative study therefore aimed to contrast the specific challenges of plastic waste collectors with those facing general waste collectors. Eleven focus group discussions (FGDs), 6–12 participants per FGD (n = 87 in total), were held with plastic main collectors and sub-collectors (4 FGDs), and general waste collectors (2 FGDs)in Greater Accra, Ghana, and waste sub-collectors (2FGDs), waste intermediaries (2FGDs) and apex plastic traders (1FGD) in Kisumu, Kenya, differentiating business types and plastic from mixed waste enterprises. Barriers, enablers, and solutions were identified through thematic coding and analysis of transcripts. We find differing SWM trajectories in Accra versus Kisumu. Domestic waste separation remains low in Kisumu, whilst Accra’s SWM system evolved from flexible to rigid plastic separation. Mixed and plastic waste collectors reported shared challenges, such as lack of crushing or transport equipment, harassment, greater hazardous faecal matter in waste streams, and lack of societal recognition. Additionally, specialist plastic waste workers in Greater Accra reported business-specific challenges, notably price volatility from seasonally variable plastic waste generation and from bulk international waste plastic imports, alongside theft of separated plastics. Accra’s informal plastic waste sub-collectors were mostly elderly women who reported occupational health challenges from bending and lifting waste. Our findings highlight the need for context-sensitive plastic SWM programmes, including fair bargaining and price regulation measures, occupational health programmes and safer diaper SWM.